405ONeutrophil-lymphocyte and platelet-lymphocyte ratios as robust prognostic markers in sarcomas: A population-based analysis of 3746 sarcoma patients from Hong Kong. (24th November 2019) - Kwan, S C S; Wong, C K H; Ho, C; Zhang, Y Z; Tse, T; Lau, Y-M; Leung, L K S; Tan, T; Loong, H
Abstract: Background: Neutrophil-lymphocyte ratio (NLR) and platelet-lymphocyte ratio (PLR) have been shown to be prognostic in various cancers. Prior reports of this in sarcomas have predominantly been made through smaller cohorts from single institutions. We investigated the prognostic implications of these indices in patients with soft-tissue (STS) and bone sarcomas using a large population-based database. Methods: A population-based retrospective database was assembled to extract pts with sarcoma, as defined as ICD-9-CM codes of bone (170.x) or/and soft tissue (171.x) who have attended clinics or hospitals of the Hong Kong Hospital Authority between Jan 2004 and Mar 2018. Eligible patients (pts) with index presentation of bone sarcoma or/and STS on or after Jan 2005 were analysed to allow 1-year window. The most recent documented lymphocyte, neutrophil, and platelet counts from the index date of sarcoma diagnosis were retrieved, and the neutrophil-lymphocyte ratio (NLR) and platelet lymphocyte ratio (PLR) were correlated with survival. Abnormal (abn) NLR and abn PLR are defined as NLR≥2.5 and PLR≥182 respectively. Restricted cubic spline plots were used to explore the shape of association between baseline NLR and PLR and all-cause mortality, fitting a restricted cubic spline function with four knots (5th, 35th, 65th, and 95th centiles). Results: Of 3746 pts identified, 3358 pts satisfied eligibility: bone n = 661, STS n = 2576, both n = 121. NLR and PLR is available for 89.93% (n = 3020) of eligible pts, amongst which 65.9% (n = 1989) had abn NLR while 47.6% (n = 1438) had abn PLR., Abn NLR and abn PLR are each associated with higher all-cause mortality (abn NLR: HR 1.698, p < 0.001, 95% CI 1.424-2.025; abn PLR: HR 1.346, p < 0.001, 95%CI 1.164-1.555) and cancer-related mortality (abn NLR: HR 1.648, p < 0.001, 95% CI 1.341-2.024; abn PLR: HR 1.430, p < 0.001, 95% CI 1.205-1.697). Conclusions: This is the largest assembled population-based sarcoma cohort in Asia. We show that NLR and PLR are robust prognostic factors, and abn NLR and PLR have negative effects on survival. More importantly, the relationship between NLR and PLR and mortality is shown to be non-linear. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.